Effectiveness of Discovery Learning Assisted by GeoGebra in Enhancing Students’ Mathematical Literacy - Sofwatun, Shofa; Nurjamil, Dedi; Dewi, Sinta Verawati (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
GeoGebra-assisted Discovery Learning offers a promising solution to the challenges of mathematical literacy. This model is not only student oriented but also encourages learners to actively and independently construct mathematical concepts and connect them to real-life experiences. This study aimed to examine the effectiveness of GeoGebra based Discovery Learning in enhancing students’ mathematical literacy and to assess their literacy level after its implementation. An experimental method with a one-group pretest–posttest design was employed. The population consisted of all tenth-grade students at SMA Negeri 1 Singaparna, and the sample was selected through cluster random sampling from class X-3. The instrument was a mathematical literacy essay test, validated by experts and tested for validity and reliability on a separate sample. Data were analyzed using descriptive statistics and N-Gain calculations with IBM SPSS Statistics 24, including the Shapiro–Wilk normality test and a one-sample t-test. The findings revealed a mean N-Gain score of 0.66 (moderate category), indicating the model’s effectiveness in improving students’ mathematical literacy. Moreover, students’ literacy levels after the intervention also fell into the moderate category. Practically, this study provides teachers with learning resources, such as teaching modules, to support instruction and foster collaborative, discovery-based learning that deepens students’ understanding of mathematical concepts.